Virus-like particles of Macrobrachium rosenbergii nodavirus: particle size and capsid protein assembly domain - Ganesan, Hagilaa; Kok, Lian Ho; Abdul Razak, Mariatulqabtiah; Chean, Yeah Yong; Wong, Chuan Loo; Goh, Zee Hong; Tan, Jia Sen; Tan, Wen Siang (Elsevier, 2022)
Macrobrachium rosenbergii nodavirus (MrNv) causes white tail disease (WTD) in the giant freshwater prawn, which poses a major issue in the aquaculture sector. The capsid protein (CP) of MrNv expressed in Escherichia coli self-assembles into virus-like particles (VLPs) with a triangulation number, T = 3. However, the region in MrNv CP that involved in the viral capsid formation has yet to be identified. In the present study, a series of N- and C-terminal MrNv CP deletion mutants were constructed based on the viral subatomic structure. These mutants were then expressed in E. coli and purified with an immobilized metal affinity chromatography (IMAC). The formation of VLPs was determined using transmission electron microscopy (TEM). The results showed that, the first 29 amino acid residues at the N-terminal end of CP are dispensable for VLP formation, but deletion of these residues produced a smaller VLP. Disruption of the CP N-terminal arm (NTA) that contains a β-annulus motif resulted in no protein expression in E. coli. The β-annulus peptide was chemically synthesized, and analysed with TEM, dynamic light scattering (DLS), size-exclusion chromatography (SEC) and native agarose gel electrophoresis, but it did not assemble into VLPs. Truncation of the entire protruding (P) domain did not disrupt the VLP formation. However, deletion of the amino acid residues involved in dimeric interaction between subunits in the shell (S) domain impaired VLP assembly. In conclusion, the minimum contiguous sequence of the CP required for VLP formation was delineated in residues 30 and 252. This study provides mechanistic insights into the assembly of MrNv VLP, which will further broaden its applications in vaccine development and nucleic acid delivery.